New Faces of Marketing In The Era of The Web: From Marketing 1.0 To Marketing 3.0 - Erragcha, Nozha; Romdhane, Rabiaa (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
In the new economic and social environment, the development of new technologies coupled with the evolution of the Internet, had a deep impact on the lifestyles of the consumers and consequently on the concepts and the practices of the Marketing. Understanding the changes undergone by the marketing with the development of digital social networks and Web 3.0 technology is essential and the way in which the marketeurs can exploit this new technology. This contribution highlights mutations of marketing techniques to align the evolution of the Internet and the changes introduced by the passage of Web1.0 Web 3.0